HIV stigma by association among Australian gay and bisexual men. (1st September 2020) - Broady, Timothy R.; Brener, Loren; Hopwood, Max; Cama, Elena; Treloar, Carla; Holt, Martin
Abstract : Objective: The negative effects of HIV stigma may extend beyond those who are HIV-positive, to people who are perceived to be at risk of HIV. This article examines HIV stigma by association among Australian gay and bisexual men (GBM). Design: Cross-sectional, online survey of 1280 Australian gay and bisexual men. This article focuses on HIV stigma from within a larger study that investigated stigma related to sexual identity. Methods: Bivariate and multivariable comparisons were made between men who experienced HIV stigma by association and those who did not. A serial mediation model was tested to investigate relationships between GBM community attachment, sexual identity stigma, HIV testing frequency, HIV stigma by association, psychological distress, and rejection of sex partners. Results: Results found that 5% of participants were HIV-positive, yet over 70% reported that they had been stigmatized by others for their perceived risk of acquiring HIV. Multivariable analysis indicated that HIV stigma by association was associated with more frequent HIV testing, greater GBM community attachment, experiencing stigma related to sexual identity and psychological distress. Our results suggest flow-on effects of HIV stigma by association, such as being more likely to reject other GBM on the basis of their HIV status or not testing for HIV. Conclusion: Our results underscore the notion that HIV stigma can have broader, negative effects on HIV-affected populations. There is a need to address HIV stigma within GBM communities and society more broadly in order to encourage HIV testing and prevention among GBM. Abstract : Supplemental Digital Content is available in the text